Modular difference logic is hard - Bjørner, Nikolaj; Blass, Andreas; Gurevich, Yuri; Musuvathi, Madan (2008)
In connection with machine arithmetic, we are interested in systems of constraints of the form x + k ≤ y + l. Over integers, the satisfiability problem for such systems is polynomial time. The problem becomes NP complete if we restrict attention to the residues for a fixed modulus N.